Competitiveness of South Asia's Container Ports : A Comprehensive Assessment of Performance, Drivers and Costs - Herrera Dappe, Matias; Suárez-Alemán, Ancor (World Bank, Washington, DC, 2018)
South Asia’s seaports are crucial to the region’s economy. The region transports 75 percent of thevalue of its exports and imports by sea. Shipments are concentrated at the 14 largest container ports, which handle close to 100 percent of total container traffic. The performance of these ports has a crucial effect on the competitiveness of the region’s trade. Even though the South Asian port sector has experienced significant changes since the late 1990s — when the governments of India, Pakistan, and Sri Lanka reformed their port sectors to allow private participation—the performance of South Asia’s ports has received little attention. The World Bank undertook a comprehensive assessment of South Asia’s container ports to support South Asian governments and stakeholders in the sector. It sought to understand the links between performance and its drivers and costs and to identify whether and how performance might be improved. The study proposes an approach for improvement based on regional and global experience.